The Influence of the Phubbing Phenomenon on Social Skills in Developing Life Skills among Social Sciences Education Students at the Indonesian University of Education - Linda Sari; Siti Nurbayani; Yeni Kurniawati (Didaktika: Jurnal Kependidikan, 2023)
Phubbing or the act of ignoring people around you by using gadgets has a significant impact on social skills. Phubbing hinders the development of essential social skills and reduces the quality of communication in daily interactions. The aim of this research is to analyze the influence of the phubbing phenomenon on social skills in improving life skills among Social Sciences Education Students at the Indonesian Education University, so that it is hoped that students will know the impact that phubbing has on their social skills. This approach uses a quantitative approach with survey methods. The results of this research show that there is a significant influence of phubbing on social skills in improving life skills. Keywords: Phubbing, Social Skills, Life Skills